Takhrij dan Fahm al Hads "Khuffat al Jannah bi al Makaarih” dalam Kitab Adab al-'Aalim wa al Muta'allim - Ishom Fuadi Fikri (Jurnal Living Hadis, 2019)
ABSTRACTThis paper aims to discuss one of the Hadith in the book "Adab al-‘Aalim wa al-Muta’allim" by KH. Hasyim As'ariy, i.e. "Khuffat al-Jannah bi al-Makaarih". The approach used is the takhrij hadith bi al-lafdzi, which is to use few words and first words in the hadith. This paper is a study of literature based on relevant literature sources and seeks to answer the question of the status of authenticity of the hadith and how to understand the hadith. The quality of the hadith is worth Saheeh as a logical consequence of the connection of the Sanad and its famous tsiqah narrators, besides the matn hadith, it also does not conflict with such hadith as narrated by other narrators who are more religious. Therefore, the hadith can be used as a shara’ proposition, where in this case KH. Hasyim As'ariy explained that among the obligations of a teacher is always to encourage himself to; 1) always increase knowledge and do good deeds in sincerity of power and effort, 2) continuous worship, 3) read, 4) study, 5) discuss, 6) make notes, 7) memorize, 8) do not waste time and his age on something that is not related to science and good deeds, except when it is primary, including; eat-drink, rest-sleep, fulfill the rights of his wife or guest, make a living according to the level of need, illness, and so on. ABSTRAKTulisan ini bertujuan untuk membahas salah satu hadis yang yang tertera di dalam kitab “Adab al-‘Aalim wa al-Muta’allim” karya  KH. Hasyim As’ariy, yakni “Khuffat al-Jannah bi al-Makaarih”. Pendekatan yang digunakan adalah takhrij hadis bi al-lafdzi, yakni menggunakan sebagaian kata dan kata pertama dalam matan hadis. Tulisan ini merupakan kajian kepustakaan berdasarkan sumber-sumber literatur yang relevan dan berusaha menjawab persoalan mengenai status keotentikan hadis dan bagaimana pemahaman hadis tersebut. Kualitas hadits tersebut adalah bernilai shahih sebagai konsekuensi logis dari adanya persambungan sanad dan para perawinya terkenal tsiqah, disamping matan haditsnya juga tidak bertentangan dengan hadits semisal yang diriwayatkan oleh perawi lainnya yang lebih tsiqah. Oleh sebab itu, hadis tersebut dapat digunakan sebagai dalil syara’, dimana dalam hal ini KH. Hasyim As’ariy menjelaskan bahwa diantara kewajiban seorang guru adalah senantiasa mendorong dirinya sendiri untuk; 1) selalu menambah pengetahuan dan beramal saleh dalam kesungguhan daya dan upaya, 2) kontinyu dalam beribadah, 3) membaca, 4) belajar, 5) berdiskusi, 6) membuat catatan-catatan, 7) mengahafal, 8) tidak menyia-nyiakan waktu dan umurnya pada sesuatu yang tidak berkaitan dengan keilmuan dan amal saleh, kecuali bila hal itu bersifat primer, diantaranya; makan-minum, istirahat-tidur, memenuhi hak istri atau tamunya, mencari nafkah sesuai kadar kebutuhan, sakit, dan sebagainya.